Assistive technology based on rahmatan lil ‘alamin principles to support visually impaired students’ academic achievement - Neni Meiyani (Lentera Negeri, 2026)
The integration of assistive technology in inclusive education has become an important approach to improving learning access for students with visual impairments. However, beyond technical functionality, its implementation also requires a value-based framework that promotes equity and compassion. Aim: This study aims to examine how assistive technology is implemented based on the principles of Rahmatan lil ‘Alamin and how it supports the academic participation of visually impaired students in inclusive classrooms. Using a qualitative descriptive approach, this study was conducted in an inclusive educational institution involving 6 visually impaired students, 3 teachers, and 2 technical support staff. Data were collected through observations, semi-structured interviews, and documentation analysis. Data were analyzed through coding, categorization, and thematic interpretation. Trustworthiness was strengthened through triangulation and peer debriefing. The findings show that assistive technologies, such as screen readers, Braille displays, and audio-based learning platforms, improved students’ access to learning materials, classroom participation, and independent study practices. Teachers reported more active engagement, while students expressed greater confidence in completing academic tasks. The integration of compassion, fairness, and collaborative support also contributed to a more inclusive learning environment, although technical barriers and the need for continued guidance remained. Value-oriented assistive technology implementation can support a more humane and responsive model of inclusive education for students with visual impairments by promoting meaningful participation and learning independence.